Case Report: Skeletal Muscle Lymphoma as a Result of Slow Centrifugal Migration of Untreated Primary Neurolymphomatosis? - Balogova, Sona; Greksak, Radoslav; Mizickova, Magdalena; Noskovicova, Lucia; Babal, Pavel; Lukac, Ludovit (Frontiers in Nuclear Medicine, 2022)
Introduction Fludeoxyglucose (18F) (FDG) hybrid positron emission tomography/computed tomography (PET/CT) is currently a well-documented tool for diagnosis, staging, and therapeutic follow-up of lymphoma with significant impact on therapeutic decisions. Patient Concerns and Interventions We reported a case of a 71-year-old woman with diffuse large B-cell lymphoma (DLBCL) of the left gluteal muscles as a possible result of slow centrifugal migration of untreated neurolymphomatosis (NL) of the lumbosacral plexus suggested on FDG PET/CT 4 years ago, when the patient was complaining for weakness and numbness of the left leg, but the proposed biopsy of peripheral nerve was not performed. Four years later, no pathological FDG uptake was present in nerves and lymph nodes, but PET/CT detected multiple FDG-positive infiltrates in the left gluteal muscles, appearing as a continuation of previously involved nerves. Diagnosis The biopsy of muscular infiltrates confirmed DLBCL. Outcomes The therapy was started, and a complete remission was achieved after three lines of treatment. Conclusion This case contributes to limited knowledge on development of skeletal muscle lymphoma (SML): It suggests the macroscopically isolated, FDG-positive SML involving more than one muscular compartment as a possible consequence of natural course of untreated primary NL previously revealed by peripheral neuropathy and suspected on FDG PET/CT. This observation further justifies the consideration of implementation of FDG PET/CT into diagnostic algorithm while evaluating the peripheral neuropathy, in which the NL, albeit rare, is a part of differential diagnosis.